A new testing method for the dynamic response of soft cellular materials under combined shear–compression. (August 2019) - Hou, B.; Xiao, R.; Sun, T.F.; Wang, Y.; Liu, J.G.; Zhao, H.; Li, Y.L.
Highlights: A new method based on the split Hopkinson pressure bar to perform dynamic combined shear–compression tests on cellular materials is presented. In this design, the output bar is rotatable to form an angle with the input bar axis to load the cellular material with dynamic combined shear–compression. This new method can provide a quite accurate measurement on the specimen forces and deformation in both shear and normal directions. The testing results with this new apparatus on a 5052 aluminum honeycomb show good reproducibility. The results at different loading angles reveal that the normal strength of honeycomb will be weakened by an increasing shear component at high strain rate loading. Abstract: This paper presents a new method based on the split Hopkinson pressure bar (SHPB) to perform dynamic combined shear–compression tests on cellular materials. For this purpose, the input bar is designed to have a beveled end at the specimen side, and the output bar is rotatable to form an angle with the input bar axis and keep perpendicular to the beveled end of input bar. The specimen is glued onto the input and output bars to avoid slippage during loading. Different shear–compression loading states can be realized by changing the beveled end of the input bar and accordingly rotating the output bar. Such a testing method is checked by simulating the whole loading process with FE model. It shows that this combined shear–compression method provides a quite accurate measurement on the specimen forces and deformation in both shear and normal directions. At last, this loading system is applied to test the shear and normal behaviors of 5052 aluminum honeycomb in TW plane at different loading angles. Good reproducibility is achieved for the applied material in terms of normal stress/normal displacement and shear stress/shear displacement curves. The experiment results reveal that the normal strength of the honeycomb will be weakened with an increasing shear component at high strain rate loading, which is consistent with our previous conclusions.